High efficacy of chlorfenapyr-based net Interceptor® G2 against pyrethroid-resistant malaria vectors from Cameroon - Magellan Tchouakui; Riccado F. Thiomela; Elysee Nchoutpouen; Benjamin D. Menze; Cyrille Ndo; Dorothy Achu; Raymond N. Tabue; Flobert Njiokou; Ateba Joel; Charles S. Wondji (BMC, 2023)
Abstract Background The increasing reports of resistance to pyrethroid insecticides associated with reduced efficacy of pyrethroid-only interventions highlight the urgency of introducing new non-pyrethroid-only control tools. Here, we investigated the performance of piperonyl-butoxide (PBO)-pyrethroid [Permanet 3.0 (P3.0)] and dual active ingredients (AI) nets [Interceptor G2 (IG2): containing pyrethroids and chlorfenapyr and Royal Guard (RG): containing pyrethroids and pyriproxyfen] compared to pyrethroid-only net Royal Sentry (RS) against pyrethroid-resistant malaria vectors in Cameroon. Methods The efficacy of these tools was firstly evaluated on Anopheles gambiae s.l. and Anopheles funestus s.l. from Gounougou, Mibellon, Mangoum, Nkolondom, and Elende using cone/tunnel assays. In addition, experimental hut trials (EHT) were performed to evaluate the performance of unwashed and 20 times washed nets in semi-field conditions. Furthermore, pyrethroid-resistant markers were genotyped in dead vs alive, blood-fed vs unfed mosquitoes after exposure to the nets to evaluate the impact of these markers on net performance. The XLSTAT software was used to calculate the various entomological outcomes and the Chi-square test was used to compare the efficacy of various nets. The odds ratio and Fisher exact test were then used to establish the statistical significance of any association between insecticide resistance markers and bed net efficacy. Results Interceptor G2 was the most effective net against wild pyrethroid-resistant An. funestus followed by Permanet 3.0. In EHT, this net induced up to 87.8% mortality [95% confidence interval (CI): 83.5-92.1%) and 55.6% (95% CI: 48.5-62.7%) after 20 washes whilst unwashed pyrethroid-only net (Royal Sentry) killed just 18.2% (95% CI: 13.4-22.9%) of host-seeking An. funestus. The unwashed Permanet 3.0 killed up to 53.8% (95% CI: 44.3-63.4%) of field-resistant mosquitoes and 47.2% (95% CI: 37.7-56.7%) when washed 20 times, and the Royal Guard 13.2% (95% CI: 9.0-17.3%) for unwashed net and 8.5% (95% CI: 5.7-11.4%) for the 20 washed net. Interceptor G2, Permanet 3.0, and Royal Guard provided better personal protection (blood-feeding inhibition 66.2%, 77.8%, and 92.8%, respectively) compared to pyrethroid-only net Royal Sentry (8.4%). Interestingly, a negative association was found between kdrw and the chlorfenapyr-based net Interceptor G2 (χ 2 = 138; P < 0.0001) with homozygote-resistant mosquitoes predominantly found in the dead ones. Conclusions The high mortality recorded with Interceptor G2 against pyrethroid-resistant malaria vectors in this study provides first semi-field evidence of high efficacy against these major malaria vectors in Cameroon encouraging the implementation of this novel net for malaria control in the country. However, the performance of this net should be established in other locations and on other major malaria vectors before implementation at a large scale. Graphical Abstract